Pengembangan Back-End Sistem Informasi Pendataan Sekolah Di Pendar Foundation - Sofyan Mufti Prasetiyo; Rifsi Baehaki; Suharjono; Maulidya Nur Ananda P. (CV. Multi Kreasi Media, 2022)
The purpose of developing a data collection information system for the Pendar Foundation Community is to facilitate the recording and grouping of data on